Analysis of Factors Related to Traffic Accidents of Adolescents in SMK Taman Siswa Mojokerto - Lutfi Wahyuni; Agus Haryanto; Faisal Ibnu (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2022)
The magnitude of the number of accidents by motorbikes affects the number of fatalities in Indonesia. Traffic accidents recently occur frequently and cause many losses. The magnitude of the number of accidents by motorbikes also affects the number of fatalities in Indonesia. Traffic accidents can occur due to human factors, vehicle factors, and environmental factors that have a major influence on traffic accidents. This study aimed to analyze the factors related to traffic accidents in adolescents. The design used analytical descriptive research design. The population in this study were all class XI students majoring in the automotive department of SMK Taman Siswa Mojokerto. The sample of 146 people was obtained by total sampling. The variables were factors related to traffic accidents in adolescents. The data were collected using primary data from respondents. After the data was collected, the data was processed and continued with descriptive statistical tests with the help of SPSS version 16.0. In this study, the human factor included the gender of the respondents, mostly male (95.2%), and most of the respondents were 14-16 years old or in the middle adolescent category (90.4%), most of the vehicle factors were complete (61%)., and environmental factors (6.4%). This was due to the lack of youth concern for driving safety on the highway. Providing information to adolescents on the causes of accidents can be done to be more vigilant and careful when driving on the highway to minimize the occurrence of accidents